Polish Experiences of Pain Treatment by Paramedics in relation to Good Practices of Pain Treatment: A Register-Based Study - Mariusz Koral; Jakub Szyller (Emergency Medicine International)
Background. Pain is frequently encountered in the prehospital setting. The treatment of pain is one of the priority activities for paramedics. Methods. 1048576 patients under the care of EMS over a 7-month period were included in this study. Data included using pain scale and pain score, the initial diagnosis, analgesic treatment and the given drug obtained from the Ambulance Emergency Procedure Cards. Results. The complete absence of pain was detected in 43.9% (95% CI 43.8–44.0) of patients, mild pain in 17.0% (95% CI 16.9–17.1), moderate pain in 11.6% (95% CI 11.5–11.7), and severe pain in 4.9% (95% CI 4.9–4.9) of cases. In 22.5% (95% CI 22.4–22.6), no pain rating scale was used. 98.0% (95% CI 97.9–98.1) of patients with mild, 96.1% (95% CI 96.0–96.2) with moderate, and 94.0% (95% CI 93.9–94.1) with severe pain did not receive any pain medication. The most commonly used drugs in all groups were metamizole and ketoprofen. The greatest analgesic effect was observed in the group of patients with severe pain. Pain decreased by an average of 3.2 NRS points in the drug-free group and 3.1 NRS points in the treated group. The most commonly documented diagnoses in all groups of patients were signs and diseases not classified in other groups (ICD-10 R00-R99), injuries and consequences of external causes (ICD-10 S00-T98), and diseases of the circulatory system (ICD-10 I00–I99). Conclusions. Paramedics may use a variety of medications but use them rarely. Adding metamizole to the list of medications used by paramedics has made it one of the most commonly used drugs. Regardless of whether the drug was used or not, the analgesic effect was similar.